Penerapan Sistem Informasi Akuntansi - Widy Hastuty HS; Agus; Maisyarah Salsabila; Nurlaila Harahap (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
Accounting Information System is a system within an organization that is responsible for preparing information obtained from collecting and processing transaction data that is useful for all users both inside and outside the company. Accounting information generated by SIA is divided into 2, namely: Financial accounting information, information in the form of financial reports addressed to external parties, Management accounting information, useful information for management in making decisions. Companies can process information more effectively and efficiently with a good accounting information system because they have control over the process, resulting in excellent quality financial reporting results. Relevant, understandable, verifiable, neutral, timely, comparable, and comprehensive financial reports of excellent quality In addition, the accounting information coming out of the accounting information system can be used in the future to make decisions about a company's financial statements or used by people outside the company, such as investors, clients, and suppliers, who are directly involved in the company's business activities. The accounting system is made to meet the information needs of both internal and external parties. The purpose of this system is to generate useful data for both internal and external parties. The company's accounting system can be processed manually (without blocking the machine) or with a computer or other machine, from a simple bookkeeping machine.